Rethinking of design excellence via building performance: with particular reference to the RIBA Award-winning schools in the UK - Chen, Yanti (2016)
Too often, buildings do not correspond to the original design aspirations of designers. This PhD project aims to investigate whether or not buildings branded as exhibiting ‘design excellence’ perform well in practice, focusing on the quality of the indoor environment and the satisfaction of occupants. It also intends to explore how to ensure that buildings with design quality achieve good performance in use.